933 Impact of first aid training on the first aid knowledge and skills capacity of primary school teachers in Ibadan, Nigeria. (1st September 2016) - Ibrahim, Abdulmumin; Sam-Agudu, Nadia; Omaye, Ugbede; Ushie, Boniface; Olumide, Adesola; Omotade, Olayemi
Abstract : Background: Acute illness and injury are major causes of child morbidity and mortality. Young children are prone to injury, and schools in developing countries are often not optimally child-proofed. In Nigeria, primary schoolteachers supervise students in an often injury-prone environment, with poor access to emergency services. First Aid (FA) can make a significant difference in outcome for a young child injured at school. This study was conducted to assess FA knowledge and skills in a cohort of primary school teachers and evaluate the effect of a training program on the cohort's FA capacity. Methods: We randomly selected 151 teachers from 16 primary schools in Ibadan. A 26-point survey and simulated scenarios graded on an 18-point scale assessed FA knowledge and skills, respectively. Based on identified gaps, a training program was developed and applied to a randomly selected subset of 70 of the 151 teachers, assigning them to intervention (N = 36) and control (N = 34). Controls were given an HIV education talk. FA knowledge and skills were measured immediately and 3 months post-intervention. FA knowledge was rated poor (<13), fair (13–17) and good (>17); skills were rated poor (<9), fair (9–11) and good (>11). Chi-square, t-test and ANOVA were used to compare means and to test for associations. Results: Respondents' mean age was 41.44 ± 9.90 years, and 95.4% had poor baseline knowledge. There was no difference in mean FA knowledge between intervention (7.69 ± 1.97) and control (7.29 ± 2.47) at baseline (p = 0.49). Mean baseline FA skills scores between intervention (0.5 ± 2.27) and control (0.65 ± 1.28) were similar (p = 0.59). Compared to baseline, there was a significant increase in mean FA knowledge immediately (20.83 ± 1.00, p < 0.001) and 3 months post intervention (18.24 ± 2.00, p < 0.001). Mean FA skills scores also improved from baseline, immediately (12.72 ± 1.80, p < 0.001) and 3 months post intervention (9.64 ± 2.03, p < 0.001). There were no significant changes in FA knowledge or skills in the control group. Conclusions: First aid knowledge and skills among primary school teachers in Ibadan was poor. The training program led to a significant and sustained improvement in teachers' FA capacity. Primary school teachers can be trained and retrained to provide appropriate and timely basic care for students injured at school.